Extended Evaluation of Virological, Immunological and Pharmacokinetic Endpoints of CELADEN: A Randomized, Placebo-Controlled Trial of Celgosivir in Dengue Fever Patients - Sung C. (Public Library of Science (PLoS), 2018)
10.1371/journal.pntd.0004851